2019
DOI: 10.1037/fam0000562
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: Maternal and paternal sensitivity to infants in four settings.

Abstract: To date, results have been inconsistent in whether mothers show higher parental sensitivity to their infant than fathers do. The context in which sensitivity is measured may play a role in these inconsistent findings, but this has not been examined yet. The aim of the current study was to test context as a source of variability in parental sensitivity, comparing maternal and paternal sensitivity to infants in four different observational settings. Participants included 109 families with their 4-month-old infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 19 publications
2
27
0
2
Order By: Relevance
“…Interestingly, the rather distinct patterns of results for fathers and mothers in this study contrasts with the broadly similar results for mothers and fathers in other analyses involving the same study sample. These include the finding that mothers and fathers provide conceptually equivalent ratings of their own symptoms of depression and anxiety ( 7 ) and do not, on average, differ in mean levels of caregiving sensitivity at 4-months ( 44 ). Other analyses from this study sample have also revealed striking between-parent similarities in: (a) the interplay between difficult birth experiences and postnatal wellbeing ( 7 ); and (b) associations between prenatal symptoms of anxiety and depression and infant adjustment at 24-months ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the rather distinct patterns of results for fathers and mothers in this study contrasts with the broadly similar results for mothers and fathers in other analyses involving the same study sample. These include the finding that mothers and fathers provide conceptually equivalent ratings of their own symptoms of depression and anxiety ( 7 ) and do not, on average, differ in mean levels of caregiving sensitivity at 4-months ( 44 ). Other analyses from this study sample have also revealed striking between-parent similarities in: (a) the interplay between difficult birth experiences and postnatal wellbeing ( 7 ); and (b) associations between prenatal symptoms of anxiety and depression and infant adjustment at 24-months ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in keeping with a general propensity to overlook fathers, Humphreys et al ( 3 ) only included mothers in their study. In an exceptional study involving mothers and fathers, Branger et al ( 44 ) found no effect of parent gender on mean levels of caregiving sensitivity observed in routine settings (e.g., lap-play) with 4-month-old infants. However, this study did not explore links between caregiving and either parental wellbeing, couple relationship satisfaction or self-focus.…”
Section: Does Self-focus Mediate the Impact Of Perinatal Wellbeing Onmentioning
confidence: 98%
“…Despite some interesting findings, our study is not without limitations. First, we used static facial expressions instead of dynamic ones (Garrido et al, 2017), which would have been closer to natural parental contexts of caregiving, enhancing the mothers' sensitivity to children facial expressions (Branger et al, 2019). Further, facial expressions presented in the tasks were of unknown children.…”
Section: Discussionmentioning
confidence: 99%
“…In the first semester of life, there are agerelated transformations in the way infants regulate their feelings and express their interests to their companions (Trevarthen and Aitken, 2003). In the same period, relevant studies comparing emotional engagement in playful interactions of infants with their mother and father did not find significant differences in parental sensitivity and synchrony, but they showed variations in emotional matching and attunement (Braungart-Rieker et al, 1998;Feldman, 2003;Kokkinaki and Vasdekis, 2015;Branger et al, 2019).…”
Section: Hypotheses and Importance Of This Studymentioning
confidence: 93%
“…Several studies have compared emotional engagement in playful interactions of infants with their mother and father in the first semester of life. Some researchers did not find significant differences in parental attempts to direct infant's attention, sensitivity and synchrony (Landerholm and Scriven, 1981;Braungart-Rieker et al, 1998;Feldman, 2003;Branger et al, 2019). Others described variations between mothers and fathers in playful behavior, responsiveness, emotional matching, and attunement (Yogman, 1981;Belsky et al, 1984;Forbes et al, 2004;Kokkinaki and Vasdekis, 2015).…”
Section: Previous Studies Comparing Emotional Engagement and Speech Amentioning
confidence: 99%